The Image and the Text in X: Multimodal Discourse Analysis in Educational Accounts - Pinilla Gómez, Raquel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
In social networks, communication reaches a dynamic character as a result of the different semiotic codes used. This research analyzes multimodal discourse in X when images (photos, videos, GIFs, memes, emojis, etc.) and texts are combined, which generates an attractive visual narrative for followers. The main objective is to identify common semiotic structures or formats in this network. The exploratory nature methodology is based on the selection of a strategic non-probabilistic sample of accounts from the educational ecosystem, selected randomly and aimed at the educational X community. The results of the analysis support the communicative tendency to use these multimodal texts that combine visual and verbal narrative in X's publications as a strategy that, therefore, deserves to be an object of study.